Innovative and networked business functions: customer-driven procurement. Issue 3 (1st May 2015) - Tunisini, Annalisa; Sebastiani, Roberta
Abstract : Purpose: – This paper aims to highlight the evolving and articulated role of purchasing as a "mediator" between the company's customers and suppliers, thus showing the opportunities connected to the evolution of purchasing from a business function to a strategic business for companies. Design/methodology/approach: – The paper reports on an in-depth analysis to investigate the case of IBM, which turned to the offering of services to transform itself from a pure product manufacturer into an outstanding service provider. Findings: – The paper shows that as the company's business strategy becomes focused on client value, its success is strongly dependent on the development of a customer-driven procurement. The evolution of the role of procurement is accompanied by the growing integration between the company's procurement and sales functions, as well as by the growing interconnection and interaction between the procurement function and the company's clients. Originality/value: – The paper applies the conceptual approach and theoretical tools connected to servitization and procurement development processes to an innovative case study. The results make possible original suggestions both for literatures and management practices.